Izrael jako mesjańska Mądrość i jej świadectwo pośród narodów w Iz 55,3-5. Studium egzegetyczo-historyczne - Zawadzki, Arnold (Collectanea Theologica, 2016)
The article tries to describe the theology of David’s testimony in Isaiah 55:3-5 in light of its historical background, to wit the last decade of the Babylonian exile, and in relation to the internal quandary of Judean Exiles. The study undertakes an inquiry into the question of whether the eternal covenant in Isaiah 55:3-5 is the continuation of the Sinaitic Covenant, or rather does its content go beyond the Mosaic Law, creating a totally new relationship of God with Israel. The study also draws attention to the existence of a redactional addition, which swifts the weight of the original message from a revanchist Judeo-centrism toward the irenic ethnic-centrism typical of the Book of Jonah.